LEVERAGING STUDENTS' RETENTION AND CREATIVITY THROUGH SCIENCE-CONTENT MUSIC IN LEARNING SOLAR SYSTEM - Regina Nur Luthfiah, - (2020)
The purpose of this research was to investigate the improvement of student's retention and creativity in learning solar system through science-content music as teaching media. As many researchers only focused on students' concept mastery problem, while less teacher and student aware about the importance of the ability of students to retain, such so-called declarative knowledge which does not only facilitates the understanding of new and related learning materials, it also helps to enhance students ' ability to analyze the nature of science issues. Also, creativity is one of the skills include on 4.0 century skill which needs to be improved. Recognizing the power of music nowadays, the author tries to dig up information about how the improvement of students' retention and creativity through this innovative teaching media, which is science-content music in learning one of science topics, solar system. In the direction of investigating the result, the method used in this research is pre- experimental with one group pre-test and post-test design. The population was 7th grade students of junior high school academic year 2019/2020 from private school 'X' and the sample taken was 50 students using convenience sampling. The instrument used consist of 30 multiple choices of objective test and CPAM rubric. According to the result, the application of science-content music has a significant improvement in students' retention in medium category (N-Gain=0.36) and good result of students' creativity (76%). As a conclude, science-content music can be considered as an alternative teaching media in learning Solar System that can be implemented in Junior Secondary Schools.